1982
DOI: 10.4141/cjas82-123
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Bioavailable Energy in Poultry Feedingstuffs: A Review

Abstract: The importance of knowing the bioavailable energy (BE) content of poultry feedingstuffs is discussed in terms of economics, feed intake and the environment. The partition of ingested dietary energy is described and the effects of nutrient intake and of the microflora of the alimentary canal are outlined. Indirect biological, physical and chemical assays for BE are described and appraised. Procedures common to several direct bioassays for BE are discussed and points to consider in choosing between total excreta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
10

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(72 citation statements)
references
References 82 publications
2
60
0
10
Order By: Relevance
“…Despite considerable efforts to develop prediction models, Sibbald (1982) reported that not all attempts to relate chemical composition and energy were successful when tested with independent data, which confirms the results obtained in the present study, as a small number of prediction equations was satisfactory to predict the values of ME of SBM for pigs when using joint independent data. -Indicates acceptance of the null hypothesis (H 0 : β 1 = 1) to models ME 4 , ME 8 , ME 9 e ME 10.…”
Section: Resultssupporting
confidence: 79%
“…Despite considerable efforts to develop prediction models, Sibbald (1982) reported that not all attempts to relate chemical composition and energy were successful when tested with independent data, which confirms the results obtained in the present study, as a small number of prediction equations was satisfactory to predict the values of ME of SBM for pigs when using joint independent data. -Indicates acceptance of the null hypothesis (H 0 : β 1 = 1) to models ME 4 , ME 8 , ME 9 e ME 10.…”
Section: Resultssupporting
confidence: 79%
“…These results were different from those of Bonnet et al (1997) and Wallis & Balnave (1984), who, in studies with broilers in heat environments, showed a consistent decrease in protein and amino acid digestibilities in complete diets. Sibbald (1982) observed that the results of many studies associating digestibility with heat stress are not conclusive.…”
Section: Diet Had No Influence On Carcass Yieldmentioning
confidence: 80%
“…A energia é fundamental para aves e um componente importante em todos os alimentos, portanto, o controle da produtividade, a eficiência e a rentabilidade exige conhecimento mais detalhado das exigências e dos valores energéticos de cada alimento (Sibbald, 1982). Segundo Freitas et al (2006), na formulação de rações, a principal preocupação é fornecer energia em quantidade adequada para as aves.…”
Section: Introductionunclassified